Languages with weak grammatical skills: A descriptive and normative - Israa Karim Sadiq Abdul, Researcher; Mudhaffar Abdul Rumi, Assistant Professor Dr. (lark, 2026)
This research examines the study of the grammatical level in weak languages through a descriptive and normative approach. It focuses on tracing and analyzing grammatical phenomena in these languages by examining the grammatical rules relied upon by linguists. The study is applied to both Quranic readings and other Arabic texts, highlighting the manifestations of linguistic weakness evident in grammatical forms, particularly in the past tense, the jussive mood, and transitivity with the hamza. The research demonstrates how these phenomena affect the structure of Arabic sentences and the meaning of verbs. It includes applied examples from Quranic texts and classical Arabic texts to Illustrate the differences that arise between various readings and grammatical styles. This research aims to understand weak languages at the grammatical level, and its detailed description combines linguistic grammatical phenomena with the grammatical standards established by grammarians, thus contributing to a broader understanding of the nature of weak languages. The research’s sIgnifIcance lies in providing a comprehensive model for studying these phenomena to interpret Quranic texts and offer a clear analysis of the grammatical structure of sentences and verbs in Arabic.